Preparation and evaluation of a chiral HPLC stationary phase based on cone calix[4]arene functionalized at the upper rim with l‐alanine units. (22nd November 2017) - Yaghoubnejad, Sadegh; Tabar Heydar, Kourosh; Ahmadi, Seyyed Hamid; Zadmard, Reza
Abstract: Here we report a new chiral stationary phase (CSP) immobilized on silica gel based on cone calix[4]arene functionalized at the upper rim with twol ‐alanine units as new chiral selector that has been used in high‐performance liquid chromatography. The CSP was prepared by covalently bonding the allyl groups at the lower rim of calix[4]arene to silica gel by thiol‐ene click chemistry reaction. Elemental analysis of the CSP showed that 120 μmol of chiral selector bonded per gram of silica gel. 1‐Hexene was used for end‐capping of unreacted mercapto groups on silica gel. Since the CSP is chemically bonded to the silica, it can be used in the normal‐phase and reversed‐phase mode and with halogenated solvents as mobile phases, if desired. The chromatographic performance of the CSP was evaluated in the enantioseparation of the 3, 5‐dinitrobenzoyl derivatives of some amino acids, diclofop‐methyl anddl ‐mandelic acid.